Ecophenomenology as Ecosophical Education: The Liminality of Swamps - Karrow, Douglas David (The Trumpeter, 2010)
Edmund Husserl, oft described father of phenomenology, issued forth a call over 100 years ago to "return to the things themselves" in an attempt to combat the prevailing and dominating tendency of philosophy over-theorizing the world. True to his call, this paper illustrates a phenomenological investigation into the author’s relationship with a fifth generation family farm in southwestern Ontario. Specially, direct and immediate encounters within a swamp as margin/al land will be explored in an attempt to characterize liminal experience as a rich site for phenomenological exploration. Revealings of the general character of liminality shed further insights into ecophenomenology as a philosophy attempting to abridge the philosophical movements of naturalism and intentionality; to more adequately pursue the relationalities between humans and their world. In the end, such a philosophy exemplifies how meditative thinking and language create the House-of-our-Being, a powerful and necessary antidote to human rootlessness and homelessness, in turn, the key to ecosophical education.